ANALISIS PERAN GURU DALAM MENGEMBANGKAN NILAI SOPAN SANTUN SISWA SEKOLAH DASAR: analisis peran guru dalam mengembangkan nilai sopan santun siswa sekolah dasar - Yulia Lestari; Eddy Noviana; Munjiatun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract: Character education in Indonesia is evolving to meet the needs of students who are not only intellectually intelligent but also possess moral values, such as good manners, which have begun to decline among elementary school students. This study aims to explain how teachers help elementary school students develop good manners. This study employs a qualitative method with a phenomenological approach. The research participants were fourth-grade homeroom teachers, the school principal, and fourth-grade students at SD Negeri 188 Pekanbaru. Data were collected through interviews and teacher observations, then analyzed using the Miles and Huberman model, which includes data collection, reduction, presentation, and drawing conclusions through triangulation of sources to ensure data validity. The research findings indicate that teachers play a crucial role in fostering students’ values of courtesy through their various functions as facilitators, motivators, role models, evaluators, counselors, classroom managers, and planners. Values of courtesy, such as respect, appreciation, and social concern, are instilled through modeling, habit formation, motivation, and practical activities within the learning process and daily interactions.